A COMPARATIVE ANALYSIS OF EPILEPSY SEIZURE TYPES AND THEIR DEMOGRAPHIC, CLINICAL, AND ELECTROENCEPHALOGRAPHIC CHARACTERISTICS IN AZERBAIJAN (2005–2009 VS. 2019–2023) - Bayramova, L.G.; Mehtiyeva, Sh.N. (World of Medicine and Biology, 2025)
This study compares the distribution of seizure types and their associated demographic, clinical, and electroencephalographic features in Azerbaijani epilepsy patients across two distinct periods: 2005–2009 and 2019–2023. A retrospective analysis was conducted on two cohorts: 322 patients (2005–2009) and 328 patients (2019–2023). Variables included seizure type (focal, generalized, unclassified), age, sex, marital status, family history, seizure frequency, etiology, and electroencephalographic findings. Focal seizures predominated in both cohorts (65.9 % vs. 57.9 %), while generalized seizures were more common among pediatric patients and those with family history. Structural etiology was strongly associated with focal seizures; genetic causes predominated in generalized seizures. Electroencephalographic findings showed clear associations with seizure type. Combination therapy increased over time. While focal seizures remain dominant, changes in genetic diagnosis and treatment preferences highlight evolving epilepsy care in Azerbaijan. These findings emphasize the need for expanded diagnostic capacity and access to newer antiepileptic drugs.
Keywords: epilepsy; seizure type; electroencephalography; focal seizures; generalised seizures; Azerbaijan